MicMac structural analysis to determine the strategic variables of the sugar agribusiness in Mexico - Villegas Vilchis, Antonio; Platas Rosado, Diego; Gallardo-López, Felipe; López-Romero, Gustavo (Revista Mexicana de Ciencias Agrícolas, 2020)
The matrix analysis software MicMac (Matrice d’Impacts Croisés Multiplication Appliqués à un Classement) matrix multiplication applied to a classification, is a tool to organize a collective reflection. It offers the possibility of describing a system with the help of a matrix that relates all its constituent elements, based on this description, this method aims to determine the main influential and dependent variables. In this case, it was used to determine the essential variables that will define the future of the sugarcane agribusiness in Mexico. This analysis was carried out in 2019 by a group of experts with experience, a high level of knowledge and decision-making from the sugar cane agribusiness, who are part of the National Commission for the Sustainable Development of Sugar Cane (CONADESUCA). Five strategic variables of greater mobility and influence and of greater dependence were identified that will define the future of the sugarcane agroindustry in Mexico: research, development, innovation and technology transfer (R+D+I+TT), diversification, production costs, productivity and competitiveness. By logical order, they define that as long as the sugarcane agribusiness in Mexico obtains or adopts and uses intelligent technologies (research plus development plus innovation plus technology transfer), diversify and offer products derived from sugarcane at competitive prices, then it will be able to increase your productivity, lower your production costs and as a consequence you will be more competitive. Failing to take these recommendations, the sugar cane agribusiness will not be competitive, becoming increasingly obsolete and will tend to disappear.